2022
DOI: 10.38053/acmj.1075349
|View full text |Cite
|
Sign up to set email alerts
|

The usability of shock index and lactate in predicting mortality in multitrauma patients presenting to the emergency department

Abstract: Objectives: This study was conducted to evaluate two simple and quickly assessed parameters such as shock index (SI) and lactate to predict in-hospital mortality in multi-trauma patients admitted to the emergency department (ED). Material and Methods:The study included a total of 93 patients who presented to the ED with multitrauma. In our retrospective study, SI was calculated by taking blood pressure and pulse values from the files of the patients recorded at the time of admission to the ED, and lactate valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, the initial assessment of the shock index and lactate level at ED admission could be used as important prognostic markers of mortality in polytrauma patients. 30 An earlier study from our center reported the necessity of blood transfusion as an early predictor of head injury and advanced age as an independent predictor of late mortality. 4 Our results differ from those of previously published studies.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the initial assessment of the shock index and lactate level at ED admission could be used as important prognostic markers of mortality in polytrauma patients. 30 An earlier study from our center reported the necessity of blood transfusion as an early predictor of head injury and advanced age as an independent predictor of late mortality. 4 Our results differ from those of previously published studies.…”
Section: Discussionmentioning
confidence: 90%
“…In a study evaluating patients admitted to the emergency department with multitrauma, SI was found to be an important predictor of mortality. The cut-off value of SI for mortality was 1.14, AUC: 0.738, 95% CI: 0.637–0.824, sensitivity 91.25%, specificity 53.85% [ 18 ]. In a study examining geriatric trauma patients admitted to the emergency department, the superiority of SI, MSI, and ASI in predicting mortality was proven.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it may differ depending on the shock index and serum lactate level measured in multitrauma patients. 20,21 When the immunomodulatory and immunotoxic effects of phototherapy were examined, it was shown that especially the number of CD4 lymphocytes increased after phototherapy.…”
Section: Discussionmentioning
confidence: 99%